The Threat of New Digital Media on Print within Durban Based Companies - Woolgar, Jamie Simone (The IIE, 2019)
The dissertation studied The Threat of New Digital Media on Print within Durban Based Companies whereby findings were extrapolated from the qualitative data collection methods, being interviews and an online survey. In the past, companies predominantly relied on print media channels to communicate their message effectively to their target audiences. However, in recent times with the integration of digital a shift has occurred. A key discovery identified was that print is declining however a demise will not occur due to key variables influencing this. Instead, a holistic marketing approach should be implemented by companies, to ensure a broader coverage of all target audiences. The study was small scaled, therefore no generalisations could be made with statistical confidence, however a key contribution was made to suggest specific recommendations and suggestions for future studies based on this topic, allowing future researchers with a base of knowledge and opinion to enable strategic direction into their research.
Keywords: Digital media; Digital communication; Digital marketing; Brand equity; Brand; Print media; Print communication